Experimental characterization of the chronic constriction injury-induced neuropathic pain model in mice - Gopalsamy, Banulata; Sambasevam, Yogesvari; Zulazmi, Nurul Atiqah; Chia, Jasmine Siew Min; Farouk, Ahmad Akira Omar; Sulaiman, Mohd Roslan; Tengku Mohamad, Tengku Azam Shah; Perimal, Enoch Kumar (Springer, 2019)
Number of ligations made in the chronic constriction injury (CCI) neuropathic pain model has raised serious concerns. We compared behavioural responses, nerve morphology and expression of pain marker, c-fos among CCI models developed with one, two, three and four ligations. The numbers of ligation(s) on sciatic nerve shows no significant difference in displaying mechanical and cold allodynia, and mechanical and thermal hyperalgesia throughout 84 days. All groups underwent similar levels of nerve degeneration post-surgery. Similar c-fos level in brain cingulate cortex, parafascicular nuclei and amygdala were observed in all CCI models compared to sham-operated group. Therefore, number of ligations does not impact intensity of pain symptoms, pathogenesis and neuronal activation. A single ligation is sufficient to develop neuropathic pain, in contrast to the established model of four ligations. This study dissects and characterises the CCI model, ascertaining a more uniform animal model to surrogate actual neuropathic pain condition.